The Effect of LDR, NPL, CAR on Return on Asset of Conventional National Commercial Bank in Indonesia - Sochib Sochib; Fetri Setya Liyundira; Ani Yulianti (International Journal of Accounting and Management Research, 2022)
Loan distribution is measured by the Loan to Deposit Ratio (LDR) and effective credit management to maintain credit collectability is measured by Non-Performance Loans (NPL). Besides that, the adequacy of the minimum capital provision is measured by a good Capital Adequacy Ratio (CAR). The purpose of this study is to prove the effect of LDR, NPL and CAR on Return on Assets (ROA). Do LDR, NPL and CAR have an effect on ROA in the 2017 to 2021 research period. The population for this study takes conventional national commercial bank entities in Indonesia during the 2017-2021 period. By using purposive sampling, a representative sample is obtained with certain criteria. This study uses a linear regression technique to examine the effect of LDR, NPL and CAR variables. The results of the study show that the Loan to Deposit Ratio and Non-Performance Loans have a significant effect on Return on Assets while the Capital Adequacy Ratio has no effect.